Ovarian tissue cryopreservation in a patient with breast cancer during pregnancy: a case report - Jiaojiao Cheng; Xiangyan Ruan; Juan Du; Fengyu Jin; Yanglu Li; Xiaowei Liu; Husheng Wang; Muqing Gu; Alfred O. Mueck (BMC, 2021)
Abstract Background Fertility preservation using ovarian tissue cryopreservation (OTC) in patients with certain diseases, especially those needing chemo- or radiotherapy, is becoming routine in various Western countries. Our hospital is the first and until now the only centre in China to use this method. The question of whether treatment of breast cancer during pregnancy (PrBC) should be similar to non-pregnant young patients with breast cancer is controversial. To our knowledge, this is the first report worldwide to use OTC as fertility preservation for PrBC. Case presentation During the 29th week of pregnancy, a 24-year-old woman underwent needle aspiration cytology of a left breast tumour. Ultrasound and cytology revealed BI-RADS 4a grade. Oncologists recommended termination of the pregnancy. Caesarean section was performed at week 32, and ovarian tissue samples were collected for OTC to preserve fertility and ovarian endocrine function. Twenty-three ovarian cortex slices were cryopreserved. It is estimated that 13,000 follicles were cryopreserved. Breast nodules and sentinel lymph node biopsy suggested invasive micropapillary carcinoma. Neoadjuvant chemotherapy was started within 1 week after diagnosis. After six courses of neoadjuvant chemotherapy, targeted drug therapy and goserelin acetate, left mastectomy and left axillary lymph node dissection were performed. In total, 23 doses of radiotherapy, eight trastuzumab targeted therapy treatments, and 17 pertuzumab + trastuzumab double targeted therapy treatments were performed after breast cancer surgery. Until now, more than 2 years after delivery, the ovarian function still is good, and no signs of a negative impact of OTC have been observed. Goserelin acetate injections, administered every 28 days, are planned to last for the next 5 years. In addition, endocrine therapy with anastrozole was started after breast cancer surgery and also is scheduled for 5 years. Conclusion OTC for fertility preservation in patients with PrBC does not delay breast surgery, radiotherapy or chemotherapy, which is essential for effective treatment of breast cancer. We assess this method as a promising fertility preservation method which was used here for the first time worldwide in a patient who developed breast cancer during pregnancy.